Anotaciones sobre la educabilidad como componente fundamental de la universidad: Perspectiva filosófica para una formación en el humanismo. (2021)
The continuous worryness of the national government and the Colombian universities to improve the quality of the education, are recognized widely. Recent policies and educative lines that determine such preoccupation, have caused that the University extends its work fields and aims to have an organization dedicated to the preparation of its students through the académic/ disciplinar instruction - was its fundamental function -, to bei an Institution dedicated to the formation, which investigation and the social projection. However, it excellent to think that such functions of the University - shaped in its curriculums- they previously need a consideration the human being, who is only possible to be made as soon as the education makes possible to think, that human being,-actor of the educative process,-of a way that totally involves it from his ontology, in addition to it distinguishes him from a gnoseological and him ethical perspective. So to speak the education is understood like a scene in which the actors involved in scene appear like different people and, therefore, the dialectic of their encounter allows them to understand that the education is possible thanks to t them as perfect human beings. Considering these reasons, is this paper which Educability, has been denominated. This text tries to look for the same conceptualización of the educability, has been approached as well proposing that this is the base of all pedagogical reflection, not only from an anthropocentric interpretation, but also from a humanist consideration. } Trough about the following lines it’s to be told the educability and its relation with the education and pedagogy, its characterization and some forms of interpretation.